TRANSFORMATIVE POWER OF ENGLISH - Joselin, Joen D; Eronimus , Amal J (International Journal of Psychosocial Rehabilitation, 2020)
Learning a language first hand or second, it needs a set of rules and regulations to be followed. Some rules are framed with a structure and many a rule is spontaneous as per the need of the students and teacher’s rapport. The following article focuses on the practical skeleton of phenomena for the learning of a language. From personal to interpersonal relationship, there are various methods to be grasped for the better performance in life as well in language, which are from the author’s point of view dealt for the future researchers to go on.